0
$\begingroup$

In describing the decomposition of the deformation gradient tensor given by $\mathbf{F}=F_{iJ}=\partial x_i/\partial X_J$, Malvern (1969, Introduction to the mechanics of a continuous medium) mentions that due to the finite nature of the displacements implied in the definition of $F_{iJ}$, it does not have an additive decomposition as the infinitesimal displacement gradient tensor ($e_{ij}$) does, given by $$e_{ij}=\partial u_i/\partial x_j=\epsilon_{ij}+\omega_{ij}\\\epsilon_{ij} = (e_{ij}+e_{ji})/2\\\omega_{ij} = (e_{ij}-e_{ji})/2.$$$F_{iJ}$ and $e_{ij}$ are defined in the reference coordinate system. Instead $F_{iJ}$ has a polar decomposition given by $\mathbf{F}=\mathbf{R}\cdot\mathbf{U}$, where $\mathbf{R}$ is the rotation tensor and $\mathbf{U}$ is the right stretch tensor. However, in between the decomposition proofs of $\mathbf{F}$ and $e_{ij}$, Malvern (1969) does an additive decomposition of the velocity gradient tensor $v_{ij}$, which is defined in spatial coordinates under finite deformation, by $$v_{ij}=\partial v_i/\partial x_j=d_{ij}+w_{ij}\\d_{ij} = (v_{ij}+v_{ji})/2\\w_{ij} = (v_{ij}-v_{ji})/2,$$ where $d_{ij}$ is the rate-of-deformation tensor and $w_{ij}$ is the vorticity tensor. My question is, if under finite deformation an additive decomposition is not possible, why does $v_{ij}$ have an additive decomposition instead of polar decomposition? This is done similarly in other textbooks. I am not a physicist so a thorough explanation is appreciated.

$\endgroup$
2
  • $\begingroup$ I suspect it's simply because $v_j = dx_j/dt$, and $dx_j$ is basically the same thing as $u_j$, whose gradient tensor does have a linear decomposition. But I don't know how to state this with more rigor (at least not off the top of my head.) $\endgroup$ – Michael Seifert Aug 4 '20 at 20:20
  • $\begingroup$ That crossed my head but if it were the case there would be no physical basis to relate the velocity gradient $v_{ij}$ and the deformation gradient $\mathbf{F}$ as is done in $v_{ij}=\mathbf{\dot{F}}\cdot\mathbf{F}^{-1}$. $\endgroup$ – Rodrigues Aug 4 '20 at 20:34
0
$\begingroup$

In the non-infinitesimal case, we have \begin{align} E_{ij} &= C_{ij}-\delta_{ij}= F^T_{ik}F_{kj}-\delta_{ij}= \frac{\partial x_k}{\partial X_i}\frac{\partial x_k}{\partial X_j}-\delta_{ij}=\\ &= \frac{\partial}{\partial X_i}(X_k+u_k)\frac{\partial}{\partial X_j}(X_k+u_k)-\delta_{ij}=\\ &= \left(\delta_{ik}+\frac{\partial u_k}{\partial X_i}\right)\left(\delta_{jk}+\frac{\partial u_k}{\partial X_j}\right)-\delta_{ij}= \\ &= \frac{\partial u_k}{\partial X_i}+\frac{\partial u_k}{\partial X_j}+\frac{\partial u_k}{\partial X_i}\frac{\partial u_k}{\partial X_j} \end{align} In the infinitesimal case $X_i\approx x_i$ and the product term is small, the relation reduces to \begin{align} E_{ij}\approx \frac{\partial u_k}{\partial x_i}+\frac{\partial u_k}{\partial x_j}=e_{ij} \end{align}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.